Fly ash slag and sludge synergistic stabilization treatment method
Through the coordinated stable curing treatment method of fly ash, slag and sludge, the problems of insufficient stability of the cured body and incomplete storage of heavy metals are solved, and efficient and economical waste treatment is achieved, and environmentally friendly standards are met.
Patent Information
- Application Number
- CN202411881292.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-19
AI Technical Summary
When the existing curing and stabilization technology treats fly ash, slag and sludge, the long-term stability and effectiveness of the cured body are insufficient, the heavy metal storage effect is limited, and the curing agent is consumed and the treatment cost is high.
The coordinated stable solidification treatment method of fly ash, slag and sludge is used to treat raw materials through centrifugal dehydration, vibrating screen and jaw crusher, mix and add appropriate amount of curing agent (such as cement, lime, bentonite), and then cure and cure under specific conditions.
It significantly improves the long-term stability and physical and mechanical properties of the cured body, effectively seals heavy metals, reduces the consumption and treatment costs of curing agents, complies with national environmental protection standards, and reduces the risk of secondary pollution to the environment.
Smart Images

Figure CN119661042A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of waste treatment and solidification, and specifically to a method for coordinated stabilization treatment of fly ash, slag and sludge. Background Art
[0002] In the context of environmental protection and resource utilization, the treatment of industrial wastes such as fly ash, slag and sludge has become a focus of current social attention. These wastes contain a large number of harmful components, such as heavy metals and organic pollutants, which will cause serious pollution to the environment if not properly treated. Traditional treatment methods mainly include solidification and stabilization technology, which aims to fix these harmful components in a solidified body through physical and chemical methods, thereby reducing their migration and release in the environment.
[0003] In the existing solidification and stabilization technology, cement, lime and other solidifying agents are used to solidify fly ash, slag and sludge into block materials. These methods adjust the type and amount of solidifying agents, as well as control the solidification and curing conditions, so that the solidified blocks have certain physical and mechanical properties and chemical stability to reduce the leaching of heavy metals.
[0004] However, due to the complexity and large variations in the composition of waste, there are still many challenges in the long-term stability and effectiveness of the solidified bodies when traditional solidification methods are used to treat these wastes. Traditional solidification methods have limited sealing effects on heavy metals, and the treated solidified bodies are prone to decreased strength and increased heavy metal leaching during long-term use. In addition, the large consumption of curing agents and high processing costs are also major defects of traditional methods, especially when dealing with large-scale industrial waste. These problems are particularly prominent. Summary of the invention
[0005] In view of the deficiencies in the prior art, the present invention provides a method for the coordinated stabilization treatment of fly ash, slag and sludge, which solves the problems of insufficient stability of the solidified body and incomplete sealing of harmful substances in the prior art.
[0006] To achieve the above objectives, the present invention is implemented through the following technical solutions: a method for synergistic stabilization of fly ash, slag and sludge, comprising the following steps: S1. Raw material pretreatment: The fly ash is dehydrated to a moisture content of less than 10% using a centrifugal dehydrator, and the fly ash and slag are processed to a particle size between 0.5-2 mm using a vibrating screen and a jaw crusher; The sludge is dehydrated using a belt filter press to a moisture content of less than 30%, and then dried in a hot air drying furnace to a moisture content of less than 10%; S2. Raw material mixing: The pretreated fly ash, slag and sludge are mixed according to a set mass ratio; S3. Add curing agent: Add the curing agent to the mixture and stir evenly; S4. Curing and maintenance: The mixture was pressed into shape and cured at 20°C ± 2°C and 60% humidity for 28 days.
[0007] Preferably, the mass ratio of the fly ash, slag and sludge is: F:R:S=40:30:30 Among them, F is the mass of fly ash, R is the mass of slag, and S is the mass of sludge.
[0008] Preferably, the curing agent is selected from one of the following: cement, lime, bentonite, and the ratio (C) of the mass of the curing agent to the mass of the fly ash is: C= in, is the mass of curing agent, is the mass of fly ash, 10%≤C≤15%.
[0009] Preferably, the process of raw material processing includes: Use a ball mill for excitation, the excitation time is 30-60 minutes, and the rotation speed is 400 RPM; Alternatively, use a vibrating mixer and mix for 20 minutes at 500 RPM.
[0010] Preferably, the process of adding a curing agent comprises: The mixture was stirred using a high shear mixer at a speed of 2000 RPM for 15 minutes; The treatment was performed using an ultrasonic processor with a power of 200 W and a treatment time of 10 minutes.
[0011] Preferably, the mold pressure during the molding of the solidified block is the ratio of the force applied during the molding of the solidified block to the mold area.
[0012] Preferably, the compressive strength test of the solidified block adopts a compression testing machine with a loading rate of 1 mm / min, and the compressive strength of the test sample should reach ≥10 MPa.
[0013] Preferably, the heavy metal content of the solidified block is tested using an atomic absorption spectrometer, and the test items include heavy metals such as Pb, Cd, and Cr.
[0014] Preferably, during the curing and curing process, the ambient temperature is maintained at 20°C±2°C and the humidity is maintained within the range of 60%±5%.
[0015] Preferably, the chemical stability of the cured block after the 28-day curing period is tested by the following indicators: pH value: The pH value of the test sample should be in the range of 6.5 to 8.5; Leachate testing: Conduct heavy metal testing on the leachate.
[0016] The present invention provides a method for the coordinated stabilization treatment of fly ash, slag and sludge. It has the following beneficial effects: 1. The present invention effectively improves the solidification effect of fly ash, slag and sludge by optimizing the ratio design and selecting a suitable solidifying agent, and solves the problem of insufficient stability of the solidified body after treatment. This method ensures that the physical and mechanical properties of the solidified body meet the expected standards, enhances the stability in long-term use, thereby effectively sealing the harmful components in the waste and reducing the risk of heavy metal leaching.
[0017] 2. The present invention significantly improves the efficiency of the curing reaction through raw material processing technology and curing agent addition technology, and solves the problem that heavy metals cannot be effectively sealed in traditional treatment methods. The cured blocks meet national environmental protection standards in terms of chemical stability and physical and mechanical properties, greatly reducing the risk of secondary pollution to soil and water bodies and protecting the ecological environment.
[0018] 3. The present invention reduces the consumption of curing agent and the overall treatment cost by optimizing the curing agent dosage and improving the utilization rate of waste resources, and solves the problem of high cost in traditional treatment methods. The method not only improves the treatment efficiency, but also reduces the volume of waste and the difficulty of treatment, thus achieving a more economical and efficient waste treatment process. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 It is a process flow chart of the present invention. DETAILED DESCRIPTION
[0020] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0021] Please see attached Figure 1 The present invention relates to a method for the coordinated stabilization of fly ash, slag and sludge, which aims to effectively reduce the migration capacity of harmful substances in fly ash, slag and sludge, and prepare a solidified material with high strength and good stability. The method comprises the following steps: Step S1: Raw material pretreatment Pretreatment of fly ash: The collected fly ash is dehydrated using a centrifugal dehydrator to reduce its moisture content to less than 10%. This process helps improve the workability of the fly ash and subsequent mixing results.
[0022] The dehydrated fly ash is passed through a vibrating screen and a jaw crusher for particle size control to ensure that the particle size of the fly ash is between 0.5-2mm. This particle size range helps to enhance the overall uniformity of the solidified material.
[0023] Sludge pretreatment: The sludge is initially dehydrated using a belt filter press to reduce its moisture content to less than 30%.
[0024] The dehydrated sludge is sent to the hot air drying furnace for further drying until its moisture content is reduced to less than 10%. The dried sludge has better fluidity and mixing properties, which is conducive to subsequent stabilization treatment.
[0025] Step S2: Raw material mixing The pretreated fly ash, slag and sludge are mixed in a certain mass ratio, the specific mass ratio is F:R:S=40:30:30 Among them, F represents the mass of fly ash, R represents the mass of slag, and S represents the mass of sludge. During the mixing process, it is necessary to ensure that the components are evenly distributed to ensure the consistency of the performance of the solidified block.
[0026] Step S3: Adding curing agent Add a curing agent to the mixture and stir evenly. The curing agent can be selected from cement, lime or bentonite, and the amount added is based on the mass of fly ash, with a ratio of 10%≤C≤15%, where C represents the ratio of the mass of the curing agent to the mass of the fly ash. The formula is as follows: C= in, is the mass of curing agent, is the mass of fly ash, 10%≤C≤15%.
[0027] Step S4: Curing and curing forming: The uniformly mixed materials are pressed into a mold to form a solidified block. The mold pressure during the solidified block molding should be controlled within an appropriate range to ensure the density and strength of the solidified block.
[0028] Maintenance: The formed solidified block is placed in an environment of 20°C±2°C and 60%±5% humidity for curing for 28 days. During the curing process, the stability of the environment should be maintained to ensure that the chemical reaction in the solidified block is fully carried out, so as to achieve the expected physical and chemical properties.
[0029] Step S5: Performance test of cured block Compressive strength test: The compressive strength of the cured block was tested using a compression tester with a loading rate of 1 mm / min. The test results showed that the compressive strength of the cured block should reach ≥10 MPa to ensure that it has sufficient mechanical properties for use in engineering applications.
[0030] Heavy metal content test: Atomic absorption spectrometer is used to detect heavy metals such as Pb, Cd, Cr, etc. that may exist in the solidified block. This test is mainly to ensure the environmental protection and safety of the solidified block and prevent the solidified block from causing secondary pollution to the environment in actual application.
[0031] Optional Enhancement Processing Steps Before the raw materials are mixed or cured, the following enhancement treatments can be performed according to specific needs to improve the performance of the cured block: Raw material handling: The mixture was excited using a ball mill for 30-60 minutes with a rotation speed controlled at 400 RPM.
[0032] Alternatively, mechanical mixing can be performed using a vibrating mixer with a mixing time of 20 minutes at a mixing speed of 500 RPM.
[0033] Add curing agent: The mixture was processed using a high shear mixer with a stirring speed set at 2000 RPM for 15 minutes.
[0034] An ultrasonic processor can also be used, with a power of 200 W and a treatment time of 10 minutes. These methods help to enhance the uniformity and reaction rate of the components within the mixture, thereby further improving the performance of the cured block.
[0035] Chemical stability test of cured blocks After the curing period, the chemical stability of the cured block is evaluated, mainly through the following indicators: pH test: The pH value of the cured mass is tested and the result should be within the range of 6.5 to 8.5 to ensure that it is chemically stable and will not have a negative impact on the environment.
[0036] Leachate detection: The solidified blocks are tested for heavy metals in the leachate to ensure that the heavy metals in the solidified blocks will not be released during use, thereby meeting environmental protection standards.
[0037] Example 1: Treatment method steps based on cement curing agent: Raw material pretreatment: Fly ash: Use a centrifugal dehydrator (3500 RPM) for 20 minutes to reduce the moisture content of fly ash to less than 10%.
[0038] Slag: Use jaw crusher to process the slag to a particle size of 0.5-2 mm.
[0039] Sludge: Dehydrate to a moisture content of less than 30% using a belt filter press (pressure 0.9 MPa), and then dry to less than 10% in a hot air drying furnace (80°C, 12 hours).
[0040] Raw material mixing: Mixing ratio: fly ash: slag: sludge = 40:30:30.
[0041] Mixing: Mix for 20 minutes using a high-efficiency mixer (500 RPM).
[0042] Add curing agent: Curing agent: cement, the mass ratio of curing agent to fly ash is 12%.
[0043] Add: Add cement evenly into the mixture and stir for 10 minutes.
[0044] Curing and maintenance: Curing: Fill the mixture into a mold, apply 2 MPa pressure, and press for 5 minutes.
[0045] Curing: Curing at 20°C±2°C, 60% humidity for 28 days.
[0046] Process parameters: Raw material processing: Use a ball mill with a rotation speed of 400 RPM and an excitation time of 45 minutes.
[0047] Add curing agent: Use high shear mixer, stirring speed 2000 RPM, stirring time 15 minutes.
[0048] Example 2: Treatment method based on lime curing agent step: Raw material pretreatment: Fly ash: Use a centrifugal dehydrator (4000 RPM) for 15 minutes to reduce the moisture content of fly ash to less than 10%.
[0049] Slag: The slag was sieved using a vibrating screen (pore size 2 mm).
[0050] Sludge: Dehydrate to a moisture content of less than 25% using a belt filter press (pressure 1.0 MPa), and then dry to less than 10% in a hot air drying furnace (85°C, 10 hours).
[0051] Raw material mixing: Mixing ratio: fly ash: slag: sludge = 35:35:30.
[0052] Mixing: Use a vibrating mixer at 500 RPM for 25 minutes.
[0053] Add curing agent: Solidifying agent: lime. The mass ratio of solidifying agent to fly ash is 10%.
[0054] Add: Add lime evenly into the mixture and stir for 15 minutes.
[0055] Curing and maintenance: Curing: Fill the mixture into a mold, apply 1.5 MPa pressure, and press for 6 minutes.
[0056] Curing: Curing at 20°C±2°C, 60% humidity for 28 days.
[0057] Process parameters: Raw material processing: Use a vibrating mixer with a stirring speed of 500 RPM and an excitation time of 30 minutes.
[0058] Add curing agent: Use ultrasonic processor with power of 200W and processing time of 12 minutes.
[0059] Example 3: Treatment method based on bentonite curing agent step: Raw material pretreatment: Fly ash: Use a centrifugal dehydrator (3500 RPM) for 25 minutes to reduce the moisture content of fly ash to less than 10%.
[0060] Slag: Use jaw crusher to process the slag to a particle size of 0.5-2 mm.
[0061] Sludge: Dehydrate to a moisture content of less than 35% using a belt filter press (pressure 0.8 MPa), and then dry to less than 10% in a hot air drying furnace (75°C, 15 hours).
[0062] Raw material mixing: Mixing ratio: fly ash: slag: sludge = 40:30:30.
[0063] Mixing: Use a high-efficiency mixer at 500 RPM for 20 minutes.
[0064] Add curing agent: Curing agent: bentonite, the mass ratio of curing agent to fly ash is 15%.
[0065] Add: Add bentonite evenly into the mixture and stir for 10 minutes.
[0066] Curing and maintenance: Curing: Fill the mixture into a mold, apply 3 MPa pressure, and press for 4 minutes.
[0067] Curing: Curing at 20°C±2°C, 60% humidity for 28 days.
[0068] Process parameters: Raw material processing: Use a ball mill with a rotation speed of 400 RPM and an excitation time of 50 minutes.
[0069] Add curing agent: Use high shear mixer, stirring speed 2000 RPM, stirring time 15 minutes.
[0070] Comparative Experimental Design Purpose of the experiment: To compare the effects of different curing agents (cement, lime, bentonite) on the synergistic stabilization of fly ash slag and sludge, and to evaluate their performance in terms of compressive strength, heavy metal stability and environmental standards.
[0071] Experimental conditions: Curing agent: cement, lime, bentonite Curing agent mass ratio: 10%-15% of fly ash Curing and curing conditions: 20°C±2°C, 60% humidity, curing for 28 days Experimental data table: Example Curing agent Curing agent to fly ash mass ratio Compressive strength(MPa) pH Pb (mg / kg) Cd (mg / kg) Cr (mg / kg) Heavy metal leaching solution concentration (mg / L) Example 1 cement 12% 12.5 7.2 20 0.5 25 0.01 Example 2 lime 10% 10.2 7.5 25 0.8 28 0.02 Example 3 Bentonite 15% 11.8 7.0 18 0.4 22 0.015 Comparative experiment No curing agent N / A 5.0 6.8 60 1.5 55 0.05 According to the table, Example 1 (cement curing agent) has the best compressive strength (12.5 MPa), which is better than Example 2 (lime curing agent, 10.2 MPa) and Example 3 (bentonite curing agent, 11.8 MPa), indicating that cement curing agent has the best effect on improving the strength of the solidified block; the pH values of all examples are in the range of 6.5 to 8.5, which meets the environmental protection standards. Among them, the pH value of Example 2 (lime curing agent) is slightly higher (7.5), which helps to stabilize the solidification of harmful substances; the heavy metal content of Example 1 (cement curing agent) and Example 3 (bentonite curing agent) is lower than that of Example 2 (lime curing agent), indicating that cement and bentonite have a better stabilization effect on heavy metals; the heavy metal leachate concentration of all examples is lower than 0.05 mg / L, among which Example 1 (cement curing agent) performs best (0.01 mg / L), showing the advantage of cement curing agent in reducing heavy metal leaching.
[0072] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for the coordinated stabilization of fly ash, slag and sludge, characterized in that: The following steps are involved: S1. Raw material pretreatment: The fly ash is dehydrated to a moisture content of less than 10% using a centrifugal dehydrator, and the fly ash and slag are processed to a particle size between 0.5-2 mm using a vibrating screen and a jaw crusher; The sludge is dehydrated using a belt filter press to a moisture content of less than 30%, and then dried in a hot air drying furnace to a moisture content of less than 10%; S2. Raw material mixing: The pretreated fly ash, slag and sludge are mixed according to a set mass ratio; S3. Add curing agent: Add the curing agent to the mixture and stir evenly; S4. Curing and maintenance: The mixture was pressed into shape and cured at 20°C ± 2°C and 60% humidity for 28 days.
2. The fly ash slag and sludge coordinated stabilization treatment method according to claim 1, characterized in that: The mass ratio of the fly ash, slag and sludge is: F:R:S=40:30:30 Among them, F is the mass of fly ash, R is the mass of slag, and S is the mass of sludge.
3. The fly ash slag and sludge coordinated stabilization treatment method according to claim 1, characterized in that: The curing agent is selected from one of the following: cement, lime, bentonite, and the ratio (C) of the mass of the curing agent to the mass of the fly ash is: C= in, is the mass of curing agent, is the mass of fly ash, 10%≤C≤15%.
4. The fly ash slag and sludge coordinated stabilization treatment method according to claim 1, characterized in that: The process of raw material processing includes: Use a ball mill for excitation, the excitation time is 30-60 minutes, and the rotation speed is 400 RPM; Alternatively, use a vibrating mixer and mix for 20 minutes at 500 RPM.
5. The fly ash slag and sludge coordinated stabilization treatment method according to claim 1, characterized in that: The process of adding the curing agent comprises: The mixture was stirred using a high shear mixer at a speed of 2000 RPM for 15 minutes; The treatment was performed using an ultrasonic processor with a power of 200 W and a treatment time of 10 minutes.
6. The fly ash slag and sludge coordinated stabilization treatment method according to claim 1, characterized in that: The mold pressure during the solidification block molding is the ratio of the force applied during the solidification block molding process to the mold area.
7. The fly ash slag and sludge coordinated stabilization treatment method according to claim 1, characterized in that: The compressive strength test of the solidified block adopts a compression testing machine with a loading rate of 1 mm / min, and the compressive strength of the test sample should reach ≥10 MPa.
8. The fly ash, slag and sludge coordinated stabilization treatment method according to claim 1, characterized in that: The heavy metal content of the solidified block is tested using an atomic absorption spectrometer, and the test items include heavy metals such as Pb, Cd, and Cr.
9. The fly ash slag and sludge coordinated stabilization treatment method according to claim 1, characterized in that: During the curing and maintenance process, the ambient temperature was maintained at 20°C±2°C and the humidity was maintained at 60%±5%.
10. The fly ash slag and sludge coordinated stabilization treatment method according to claim 1, characterized in that: The chemical stability of the cured block after the 28-day curing period was tested by the following indicators: pH value: The pH value of the test sample should be in the range of 6.5 to 8.5; Leachate testing: Conduct heavy metal testing on the leachate.
Citation Information
Patent Citations
Curing method of copper sludge
CN103011738A
Sludge autoclaved brick and preparation method thereof
CN103449796A
Fly ash solidification and stabilization treatment method
CN104785490A
Method for making bricks from furnace slag and fly ash
CN110255998A
Method of treating steel making slag and sand-washing sludge
JP2002086121A
Cited By
Fly ash slag and sludge synergistic stabilization treatment method
CN120590011A